Postpartum depression associated with sex preference among rural Bangladeshi mothers - Chowdhury, Tanjida; Islam, M. Nazrul (International Journal of Research in Medical Sciences, 2024)
Background: Maternal depression, particularly postpartum depression (PPD), significantly impacts women’s well-being and can have long-term effects on child health, development, and behavior. The purpose of this study was to evaluate the association between postpartum depression and sex preference among rural Bangladeshi mothers. The aim of the study was to evaluate the association between postpartum depression and sex preference among rural Bangladeshi mothers. Methods: This cross-sectional study, conducted in Banchanagar village, Laxmipur District, Bangladesh, from January to December 2014, focused on postpartum depression among rural mothers with children aged 0-12 months and its association with sex preference. A total of 219 postpartum women, aged 15-49 years, participated. Data were collected using a pre-tested, semi-structured questionnaire, including the Edinburgh postnatal depression scale (EPDS), with double data entry and analysis in SPSS. Results: Of the 219 mothers, most had a wanted pregnancy (87.20%), with 60% experiencing complications during pregnancy. Most had no family history of depression, and a majority showed a low probability of depression. Over half considered the sex of the child, with most satisfied with it. Logistic regression showed that the sex of the child, the husband’s views, and the mother’s satisfaction were significant factors influencing postpartum depression. Conclusions: In rural Bangladesh, postpartum depression is notably higher among mothers who give birth to female children, driven by strong cultural preferences for male offspring and negative family reactions toward daughters.